Integration of Islamic Economics and Wisdom Local in Management of Damar Plantations for Increase Prosperity and Harmony Interfaith Religion in Pakel Village Gucialit District, Lumajang Regency - Ramadhani, Kurniawan (Ashfiya Journal of Qualitative Insight in Islamic Studies, 2025)
This study aims to analyze the integration of Islamic economic principles and local wisdom in damar plantation management in Pakel Guci Alit Village, as well as its implications for community welfare and interreligious harmony. Historically, the village's economic activities are closely linked to damar cultivation, which not only functions as the main economic source but also serves as a social arena fostering solidarity, tolerance, and community cohesion. Using a qualitative phenomenological approach, this research explores the experiences, perceptions, and collective meanings of community members through in-depth interviews, field observations, and participatory documentation. The findings indicate that the integration of sharia economic principles such as justice, trustworthiness, shura (consultation), proportional distribution, and prohibition of exploitation aligns with local wisdom practices including mutual cooperation, collective decision-making, and traditional communal rituals. These combined values create a sustainable, equitable, and inclusive economic governance system. The study further reveals that such value integration enhances not only economic productivity but also strengthens interreligious harmony, as socio-economic interactions occur within an ethical framework shared by all community members. This research contributes a new conceptual model of community-based economic development rooted in the synergy between religious values and local wisdom as a viable strategy for sustainable rural development.